Discovering Che-1/AATF: a new attractive target for cancer therapy - Iezzi, Simona; Fanciulli, Maurizio (Frontiers in Genetics, 2015)
The transcriptional cofactor Che-1/AATF is currently emerging as an important component of the DNA damage response machinery, the complex signaling network that maintains genome integrity and prevents tumorigenesis. Moreover this protein is involved in a wide range of cellular pathways, regulating proliferation and survival in both physiological and pathological conditions. Notably, some evidence indicates that dysregulation of Che-1/AATF levels are associated with the transformation process and elevated levels of Che-1/AATF are required for tumor cell survival. It is for these reasons that Che-1/AATF has been regarded as an attractive, still theoretical, therapeutic target for cancer treatments. In this review, we will provide an updated overview of Che-1/AATF activities, from transcriptional regulation to DNA damage response.